Effects of a flywheel-based post-activation performance enhancement warm-up versus a traditional rowing ergometer warm-up on 500 m rowing and neuromuscular performance - Thongchai, P.; Koedsiri, N.; Johansen, S.; Manosukhumnon, S.; Santalunai, A.; Zacca, R.; Van Dung, D.; Chainok, P. (European Journal of Human Movement, 2025)
Post-activation performance enhancement using flywheel exercises offers substantial immediate consequences on neuromuscular responses and mechanical adaptations. The study aimed to verify the effect of two different post-activation performance enhancement (PAPE) protocols on 500 m rowing ergometer and neuromuscular performance in collegiate rowers. Sixteenth healthy collegiate male rowers (age: 20.7 ± 2.1 years; weight: 69.9 ± 14.2 kg; height: 1.7 ± 0.1 m; BMI: 24.4 ± 3.7 kg·m2) participated in this study. Two different PAPE protocols were randomly administered: i) a general warm-up utilizing a rowing machine (control) and ii) a flywheel protocol encompassing 2 sets of 10 repetitions of biceps curl and high-pull at lower inertial loads (0.1176 kg·m2 to 0.1568 kg·m2). No changes were observed between the two warm-up protocols concerning rowing performance and physiological variables throughout the 500 m rowing time trial. The 500 m rowing time in the flywheel warm-up showed a variance of 3.70 % compared to the general warm-up, with no differences observed among the protocols (p = 0.09; 95 % CI = -0.63, 7.04; d = 0.60: medium). The observed mean differences included a peak force of IMTP at 13.2% (p = 0.03; d = -0.81; large) and an average rate of force development of IMTP at -21.6 % (p = 0.04; d = -0.53; moderate) after the 500 m rowing time trial. Nonetheless, no substantial correlations were observed between 500 m rowing time and the neuromuscular performance parameters elicited by either warm-up procedure. This study indicated that both general and flywheel warm-ups are equally effective in enhancing PAPE neuromuscular performance, with the 500 m rowing time showing slightly advantage and lead to an acute positive effect after the flywheel warm-up compared to the general rowing machine warm-up. Coaches and sport scientists may use these findings to inform acute effect consisting of flywheel-based warm-up prior to a sport-specific task of 500 m rowing.